Steatocystoma multiplex masquerading as neurofibromas - Neha Chandrakumar Bhatt; Siddhi Gaurish Sinai Khandeparkar; Avinash Joshi; Amit Bhoge (Wolters Kluwer Medknow Publications, 2014)
A 26-year-old female patient presented with multiple, smooth, round to oval, well-defined, and skin-colored nodules, without central punctum, over both axillae since past 5 years. Few nodules were observed on chest, right upper arm, and left upper thigh. No other ectodermal abnormalities were observed in the patient. There was no family history of similar lesions. A clinical diagnosis of multiple neurofibromas was made, and largest of the lesion was excised. Histopathological examination showed features of steatocystoma multiplex. Steatocystoma multiplex is an extremely rare cystic disorder of pilosebaceous units. Although previously regarded as an inherited autosomal dominant disorder, sporadic cases have been reported.